2018
DOI: 10.1155/2018/9097363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiwalled Carbon Nanotubes and Biostimulators on Growth and Content of Bioactive Constituents of Karkade (Hibiscus sabdariffa L.)

Abstract: This work was carried out to evaluate the effect of different concentrations of multiwalled carbon nanotubes (MWCNT), 0, 500, and 1000 mg/L, and biostimulators (Delfan plus), 0 and 10 ml/L, and their interactions (sprayed on the plant shoot and soil until the complete wetness) on growth and production of bioactive constituents of karkade (Hibiscus sabdariffa L.) planted in plastic pots. After finishing experiment, growth parameters (length of shoot and root, number of leaves, branches, and fruits, chlorophyll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These radicals are characteristic of disordered regions of MWCNTs, which conforms the nucleation sites for hydrogen atoms. Other signals attributed to stretch vibrations of C-H at ~2,200 cm −1 and C–H X groups of the disordered sp3 region and vibration rings at 600 cm −1 were characteristics of MWCNTs ( Al-Rekaby, 2018 ; Lehman et al, 2011 ). Conversely, we observed that the FTIR spectra of the culture residue from P. ostreatus cultivated with MWCNTs + lignin indicated the absence of the characteristic bands of the MWCNTs, also a characteristic peak of the COOH functional radicals was identified at ~1,700 cm −1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These radicals are characteristic of disordered regions of MWCNTs, which conforms the nucleation sites for hydrogen atoms. Other signals attributed to stretch vibrations of C-H at ~2,200 cm −1 and C–H X groups of the disordered sp3 region and vibration rings at 600 cm −1 were characteristics of MWCNTs ( Al-Rekaby, 2018 ; Lehman et al, 2011 ). Conversely, we observed that the FTIR spectra of the culture residue from P. ostreatus cultivated with MWCNTs + lignin indicated the absence of the characteristic bands of the MWCNTs, also a characteristic peak of the COOH functional radicals was identified at ~1,700 cm −1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…, Rekaby -Layth Sareea Al 4 detention and the relative area of the compounds, The obvious differences showed the effect of treatments with nano fertilizers and bio fertilizers on the content of the plant root. The goldenrods was represented by an increase in the proportions of some compounds over others, the emergence of new compounds, and the disappearance of others, according to the statistical analysis data presented in Table (1 The results of the statistical analysis presented in Table (2) for the compound Stigmasta-7,16-dien-3-ol, (3.beta)) were found in the root of the Goldenrods plant for the compounds that were detected in the data of the GC Mas device, which was the retention time (34.151), as the addition of the nano fertilizer at a concentration of 1 gm/ L showed an increase in the percentage of the compound, but it was not significant, as it was recorded at 6.82, and when the concentration of the nano fertilizer was increased to 2 gm/ L, the percentage of the compound decreased until it reached a ratio of 4.23 compared to the comparison plants. It scored 6.05, as for the use of bio fertilizer, it led to an increase in the compound percentage, but it was not significant, as it achieved a percentage of 6.00 compared to the comparison plants, which recorded 5.40.…”
Section: Gc-mass Analysis Of Root Extracts Goldenrodsmentioning
confidence: 99%
“…The Nanotubes treatment caused a significant variations in all measured parameters. GC-MS analysis shows quantitative and qualitative change of bioactive compounds [2]. also bio-fertilizers are also utilized as inducers to improve the synthesis of secondary metabolites in medicinal plants [16].…”
Section: -Introductionmentioning
confidence: 99%
“…Nandagopalan et al (2015) used the GC-MS technique to determine the possible chemical components in the methanol extract of Hibiscus tiliaceuss, which revealed the presence of N, N-Dimethylglycine (83.97%), 3,7,11,15 Tetramethyl-2 hexadecen-1-ol (2.94%), 4HPyran-4-one, and 2,3-dihydro-3,5 dihydroxy-6-methyl (2.69%), providing scientific proof of the plant's anti-bacterial, anti-angiogenic, anti-oxidant, and anti-diabetic qualities. Al-Rekaby (2018) carried out a work to evaluate the bioactive constituents of karkade (Hibiscus sabdariffa) where he identified four bioactive constituents: 3,7,11,15-tetramethyl-2-hexadecen-1-ol; 1,1-bicyclohexyl, 2-(2-methylpropyl)-trans; 3-buten-2-one,4-(2-hydroxy-2,6,6-trimethylcyclohexyl); and 1,2benzenedicarboxylic acid, diisooctyl ester, 6,. The objective of the study is to characterize the chemical compounds of roselle by GC-MS.…”
Section: Introductionmentioning
confidence: 99%